Most Americans Do Not Believe That There Is An Association Between Health Care Prices And Quality Of Care - Phillips, Kathryn A (Health Aff (Millwood), 2016)
Many organizations are developing health care price information tools for consumers. However, consumers may avoid low-price care if they perceive price to be associated with quality. We conducted a nationally representative survey to examine whether consumers perceive that price and quality are associated and whether the way in which questions are framed affects consumers’ responses. Most Americans (58–71 percent, depending on question framing) did not think that price and quality are associated, but a substantial minority did perceive an association (21–24 percent) or were unsure if there was one (8–16 percent). Responses to questions framed in terms of high price and high quality differed from responses to questions framed in terms of low price and low quality. People who had compared prices were more likely than those who have not compared prices to perceive that price and quality were associated. We explore implications of these findings, including how behavioral economics can inform approaches to helping consumers use price and quality information.